The Effect of Ethanolic The effect of ethanolic extract of Saffron (Crocus sativus L.) on improving the spatial memory parameters in the experimental models of Parkinson disease in male rats - Homeyra Hatami; Gholamreza Dehghan (Fasa University of Medical Sciences, 2015)
Background & Objective: The axial role of the oxidative stress in the pathophysiology of Parkinson disease has been identified. On the other hand, the learning and memory impairment in Parkinson disease has a distinguished outlook. Since Saffron has antioxidative stress effects, the aim of the present study is to investigate the improving effects of Saffron extract on the spatial memory parameters in the experimental models of Parkinson disease in male rats. Methods & Materials: In this experimental study, 35 male rats weighing approximately 250±50 gram were randomly divided in five equal groups: control, sham (saline + ascorbat), Parkinson;#39s model (injection of 6-OHDA, 2/5 μg/ μl) and 2 groups of Parkinson;#39s model + saffron extract pretreatment (5 and 10 μg/rat for 5 days). The Parkinson's induction model was made by intracerebral injection of 6 - hydroxy dopamine. The Morris Water maze was used for studying the spatial learning and memory.  The data analysis was performed by using One-Way ANOVA. Results: Intracerebral injection of 6- hydroxy dopamine increased the time latency required for finding the hidden platform and damaged the spatial memory (P<0.05). The pretreatment of Saffron extract (5 and 10 μg/rat, 5 days) improved the reduced spatial memory in Parkinson;#39s rats (P < 0.05). Conclusion: The Saffron extract is able to restore the spatial memory parameters such as the time latency and the distance travelled for finding the hidden platform in Parkinson;#39s rats as compared to the level of the control group.